Zorba the Greek - Kazantzakis, Nikos, 1883-1957.; Wildman, Carl. (New York : Scribner Paperback Fiction, 1996)
Portrait of a modern hero whose capacity to live each moment to its fullest is revealed in a series of adventures in Crete.
Originally published: New York : Simon and Schuster, 1953.
Keywords: Greek fiction -- Translations into English; Greece -- Fiction; Picaresque literature